Properties and antioxidant activity of soy protein concentrate films incorporated with red grape extract processed by casting and compression molding - Ciannamea, Emiliano Manuel (2016)
Self-standing transparent soy protein concentrate (SPC) films plasticized by glycerol (30% w/w SPC dry basis) and supplemented with red grape extract (RGE) as natural antioxidant (0e10% w/w SPC dry basis) were prepared by two methods: casting and intensive mixing followed by compression molding. The influence of RGE on key film properties was analyzed at the light of the specific stabilizing interactions of SPC films. The addition of RGE had a favorable effect on moisture content, total soluble matter, water vapor permeability and percentage of elongation of casted films compare with compression molded counterparts. RGE induced a redistribution of hydrogen interactions of casted films replacing protein protein hydrogen interactions by protein-polyphenol ones with no variations in disulfide bridges, while these last interactions were significantly reduced in compression molded films in favor of hydrophobicand hydrogen interactions, as disclosed by differential solubility assays and infrared spectroscopy. The antioxidant activity of the SPC films in terms of scavenging activity of the stable free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power, increased significantlyirrespective of the manufacturing method, being the release of antioxidants from casted films lower than that from compression molded films in accordance with the strong interactions between SPC matrix and polyphenols.